Implementasi Metode Rule Based dan TOPSIS pada Sistem Seleksi Kinerja Divisi Berdasarkan Corporate Culture - Achmad Aries Pirnando; Ignatius Joko Dewanto; Winarno Winarno (Ikatan Ahli Informatika Indonesia, 2019)
Corporate culture can be used as an effective driving force in achieving goals in accordance with the organization's vision and mission. An effective work culture can unite the ways of thinking, behaving and acting throughout the organization, making it easier to establish and implement the vision, mission and strategy in the corporation, and able to strengthen teamwork within the corporation, and eliminate internal frictions that arise. As one of the steps to maintain the existence of the company amid uncertain global conditions, it is necessary to evaluate the organization of its divisions to always cling to Corporate Culture. Based on the evaluation evaluation conducted previously, almost 50% of employees at PT XYZ Laboratories disagreed with the research conducted by the division. Therefore, it is necessary to develop a system that can act as a transparency in management decision making. By using the rule based method that is used as a selection method and the TOPSIS method that is carried out for division decision making is chosen, it is hoped that this system can be useful and in accordance with management needs. After going through the testing process, in general this system produces a total percentage of 100% on the success of the item test in the testing process of the 10 items tested. Thus the application meets the requirements for making the program, which is readable and valid.